Studies on the biology of the economic marine red alga Gelidium pristoides (Turner) Kuetzing (Gelidiales : Rhodophyta) - Carter, Alan Robert (Rhodes University, Faculty of Science, Botany Department, 1987)
Various aspects of the biology of the intertidal agarophyte, Gelidium pristoides, were investigated, with the aim of providing information that would assist in formulating a management policy for this economic seaweed resource. G.pristoides occurs as tufts comprising as many as 40 individual plants, representing all three conspicuous life history stages, that are linked by the intertwining of their basal creeping axes. Individual plants consist of a system of branched creeping axes, which is largely responsible for colonizing surrounding substrata, from which one or more erect flattened fronds arise. These erect fronds may reach a height of 15 cm, and are irregularly bipinnately branched. Internal vegetative anatomy is generally typical of the genus. Morphological variation in mature plants is limited to increased plant height and branch density during the summer season. A dorso-ventrally flattened creeping habit was seen during early recruitment on flat rock surfaces and limpet shells within grazer exclusion plots, which developed into typical erect plants. Although there is a close taxonomic affinity between G.pristoides and the low-growing Gelidium turf, which occurs on wave-cut platforms in the eastern Cape (both produce bispores), the turf appears to represent a genetically divergent ecotype of the typical G.pristoides habit. In the light of present observations, it is suggested that the recent inclusion of G.pristoides in the new Onikusa genus should be questioned. Reproduction in G.pristoides is typical of the genus, except for the production of bispores, instead of tetraspores, in the sporophyte generation. The smaller nuclei in the binucleate bispores, in comparison to carpospores, suggested they are the product of normal meiosis (meiospores). This was confi rmed by chromosome counts of germl i ngs deri ved from bispores (n = 13-17) and carpospores (2n = 28-33). Throughout the geographical range of the seaweed, the bisporophyte generation is dominant over the combined male and female gametophyte generati on by a ratio of about 3 : 1. This imbalance may be due to bispores. G.pristoides a greater germination success of carpospores over plants are fertile throughout the year, while at Port Alfred there is no apparent seasonality in spore release. Growth of carpospore and bispore germlings is similar under various temperature treatments in culture. Optimum temperatures for growth were from 15-23Â°C, which corresponds with the sea temperatures experienced within the geographical range of the species . At Port Alfred, growth (linear frond elongation) and standing crop levels were maximal during summer . Ory weight levels were significantly inversely related to both growth and ash levels. Agar contents (% of dry weight) were generally greater in summer (48% ) than in winter (30%), and were inversely correlated with thallus nitrogen levels. Agar contents of distal plant halves were higher (8-15%) than in proximal halves. Regrowth of G.pristoides to original biomass or standing crop levels after harvesting, is similar for plucking and shearing at different times of the year. Regrowth is more rapid after spring and summer harvests (2-3 months) than after winter harvests (4-5 months). During the summer season, harvesting at monthly intervals showed significantly greater total yields, and production rates (e.g . 3.13 g. dry wt. / m2 / day for plucking) than under 3-monthly intervals (1.42 g. dry wt. / m2 / day for plucking). In contrast, average yields per harvest were Significantly greater when recovery period was longer (e.g. 3 months). Quadrats that were completely denuded failed to recover after a year, while regrowth was also retarded with increased elevation on the shore. Agar contents did not differ Significantly between plucked (38%) and sheared (42%) plant material. G.pristoides is distributed from about 0 . 2-0.75 m above MLWS, with a reduction in stature and frequency corresponding to increased elevation on the shore. Frond elongation rates, germling survival and recruitment within grazer-exclusion plots, is retarded with increased elevation level. Plants transplanted above the normal vertical range of the seaweed became severely bleached and died, while plants transplanted below the normal range of the seaweed (sub littoral fringe) senesced due to overgrowth by the epiphytic encrusting coralline, Polyporolithon patena (Hook . et Harv . ) Mason . G.pristoides recrui t ment in the sublittoral fri nge was enhanced with the exclusion of grazers . However, successful recruits were displaced due to smothering by articulated corallines (e.g. Corallina sp. and Jania sp. ) . G.pristoides is largely restricted to cracks and crevices in the rock, and also occurs on a large proportion of the available shells of the limpet Patella oculus Born., and to a lesser extent, shells of the barnacle Tetraclita serrata. G.pristoides recruitment was significantly enhanced by the exclusion of grazers (using toxic antifouling paint barriers). G.pristoides recruitment within the exclusion plots was significantly greater on artificially attached limpet shells (almost 100% cover) than on rock surfaces (20-30% cover), which occurred largely within cracks and crevies in the rocky substratum. ly attached to limpet G.pristoides plants are significantly more strongand barnacle shells than to rock and epilithic encrusting corallines (Lithothamnion sp.). Removal of G.pristoides from limpet shells revealed pits of a uniform size in the surface of the shells, into which the rhizoidal attachment organs of the seaweed penetrate. It is concluded that the horizontal distribution of G.pristoides is largely controlled by grazers (and "escapes" from grazing) and resistance to dislodgement by wave action. Based on present results, and considering some of the socio-economic factors associated with the Gelidium industry in South Africa, suggestions are made concerning the management and long-term maintenance of G.pristoides resources in the eastern Cape.
Keywords: Red algae; Marine algae